CHALLENGES IN A SECOND AUTOPSY CASE AND PROPOSED GUIDELINES - Chaudhari, Vinod Ashok; Ayyappan, Sathish; Das, Siddhartha; Badhe, Bhawana Ashok (Journal of Forensic Medicine and Toxicology, 2023)
A second autopsy is a repeat examination of an autopsied body by another forensic expert or a panel of doctors, done on the orders of government officials or a court. A second autopsy is usually done whenever there is suspicious foul play, particularly in cases like homicides, custodial deaths, death overseas, etc. But recently, it has been done more often at the request of the deceased relatives when they are not convinced by the first autopsy. Here we discuss a case of a 39 years old male with a history of seizures in police custody. He was treated and sent back to police custody. After 2-3 days of discharge, he developed seizures again and was taken to a hospital, declared brought dead. The relatives were unsatisfied with the first autopsy and demanded a second autopsy which was performed 21 days after the first autopsy. In the second autopsy, the cause of death was not opined due to multiple artefacts produced during the first autopsy and decomposition changes. Since national guidelines for the second autopsy in India are not yet laid down, such cases have been reported frequently. Second autopsy cases are challenging for autopsy surgeons, and incidences are high due to improper training or faulty procedures followed during the first autopsy. This article highlights various challenges and medicolegal issues faced by autopsy surgeons or medical officers at community health centre levels during the second autopsy and the need for framing formidable guidelines for conducting a second autopsy.